Clinical features of drug abuse that reflect genetic risk. Issue 12 (24th January 2014) - Kendler, K. S.; Ohlsson, H.; Sundquist, K.; Sundquist, J.
Abstract : Background: Drug abuse (DA) is a clinically heterogeneous syndrome. Can we, in a large epidemiological sample, identify clinical features of DA cases that index genetic risk? Method: Using registration in medical, legal or pharmacy records, we identified four kinds of relative pairs ( n = 935 854) starting with a proband with DA: monozygotic co-twins; full siblings; half-siblings; and cousins. Using linear hazard regression, we examined the interaction between three clinical features of DA in the proband and risk for DA in these four relative pairs, ordered by degree of genetic relationship. Results: Increased risk for DA in relatives was robustly predicted by early age at first registration, total number of registrations, and ascertainment in the criminal versus the medical or pharmacy registry. In multivariate models, all three of these variables remained significant and in aggregate strongly predicted DA risk in relatives. The risk for DA in siblings of DA probands in the highest decile of genetic risk predicted by our three indices was more than twice as great as that predicted in siblings of probands in the lowest decile of risk. Conclusions: In an epidemiological sample, genetic risk for DA can be substantially indexed by simple clinical and historical variables.